Putting content online : a practical guide for libraries - Jordan, Mark (Mark Jerrid) (Chandos information professional series., 2006)
This book focuses on practical, standards-based approaches to planning, executing and managing projects in which libraries and other cultural institutions digitize material and make it available on the web (or make collections of born-digital material available). Topics include evaluating material for digitization, intellectual property issues, metadata standards, digital library content management systems, search and retrieval considerations, project management, project operations, proposal writing, and libraries' emerging role as publishers. Highly practical. Explains complex processes, warns of potential challenges and provides advice for solving realistic problemsComprehensive: includes coverage of the range of techniques and strategies for digitizing and organizing material that practitioners can use to plan and implement digitization projects.